PERAN MEDIASI INTELLECTUAL CAPITAL DALAM CORPORATE GOVERNANCE TERHADAP KINERJA DAN NILAI PERUSAHAAN DI INDONESIA - Sheila Adriani; Hersugondo Hersugondo (Faculty of Economics and Business Diponegoro University, 2022)
This study aims to examine the mediating role of Intellectual Capital in Corporate Governance and Performance of Companies listed on the Indonesia Stock Exchange. The sample of this study is LQ45 companies listed on the IDX in 2015-2019, which were determined using the purposive sampling method. This study uses 75 observations from 15 companies. The data used in this study is secondary data taken from the official website of the Indonesia Stock Exchange, the company's financial and annual reports, and the Bloomberg database. The analytical technique used in this research is SEM analysis using AMOS SPSS 24 software. The results of this study indicate that only Board Size can be bridged by VAIC to influence Tobin's Q, with varying results of the effect between variables.